2020
DOI: 10.1139/cjm-2018-0599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical oxygen demand load on the nitrification and microbial communities in activated sludge from an aerobic nitrifying reactor

Abstract: In this study, we explored the effect of chemical oxygen demand (COD) load on the nitrification and microbial communities in activated sludge isolated from an aerobic nitrifying tank. The activated sludge was cultured in three different COD groups: L-COD, 200 mg/L; M-COD, 1200 mg/L; H-COD, 4200 mg/L. The results indicated that the COD exerts a negligible effect on the nitrogen removal ability within the first 24 h. However, the nitrification rate decreased with culture time; the ammonium degradation rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Meron et al (2011) examined changes in bacterial communities in the coral mucus, tissue and skeleton following exposure of the coral Acropora eurystoma to two different pH conditions: 7.3 and 8.2 (ambient seawater) and found that the microbial community was different at the two pH values and an increase in bacteria associated with diseased and stressed corals in the corals maintained at the lower pH. The activated sludge in the different chemical oxygen demand groups exhibited similar community compositions after 24 h, while a significant difference in the relative abundances of some organisms occurred after 48 and 72 h (Li et al, 2020). COD Mn , Chla and Total-N were the most appropriate parameters to describe the environmental interpretation of bacterial ordinations and COD Mn was the predominant factor (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Meron et al (2011) examined changes in bacterial communities in the coral mucus, tissue and skeleton following exposure of the coral Acropora eurystoma to two different pH conditions: 7.3 and 8.2 (ambient seawater) and found that the microbial community was different at the two pH values and an increase in bacteria associated with diseased and stressed corals in the corals maintained at the lower pH. The activated sludge in the different chemical oxygen demand groups exhibited similar community compositions after 24 h, while a significant difference in the relative abundances of some organisms occurred after 48 and 72 h (Li et al, 2020). COD Mn , Chla and Total-N were the most appropriate parameters to describe the environmental interpretation of bacterial ordinations and COD Mn was the predominant factor (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…And the gap between them gradually narrowed to 5.09 mg N/(L•h) from 13.39 mg N/(L•h). Exist of organic in influent not only act as a disincentive to nitrification of nitrifiers but also change the microbial community structure in system (Li et al, 2020). Both of them weaken the NH 4 + -N removal rates of experiment.…”
Section: Removal Rate Of Nh 4 + -N With Sewagementioning
confidence: 99%
“…Inclusively, the declining COD removal kinetics coupled with temporal changes in operational parameters and microbial community structure underscores the importance of stability for optimizing activated sludge performance. A balanced mixed community with high functional redundancy appears critical to maintain treatment resilience and consistency longterm performance of treatment (Li et al, 2020). The present exertion of study as shown in Table 4 employed an activated sludge system with controlled operational parameters of MLSS, SVI, and F/M ratio to achieve 78.57% COD removal during early-stage treatment of synthetic wastewater.…”
Section: Observed Microbial Dynamicsmentioning
confidence: 99%